Ajuste a los parámetros de resistencia de depósitos de coluviones mediante correlaciones entre ensayos de laboratorio, exploración geotécnica y retrocálculo (2013)
The resistance to shear stress is a parameter that is strongly influenced by in-situ conditions; One of the most influential parameters is the water content which varies over time and according to the properties of the material. This makes it difficult to obtain representative samples under unsaturated conditions, thus generating distortions in the values ​​of the resistance parameters and generating bumps that the engineer has had to face in practice. The present investigation was motivated by the discrepancy in data obtained with laboratory and field tests in relation to the data obtained through the analysis of retrocalculation. The above is the starting point to determine a correction factor to the experimental data, which allows to see values ​​closer to the real conditions in-situ at the time of failure. It has as a database of analysis, geotechnical studies carried out in the last six years by the company Geotecnia & Cimentaciones to the sector of the Bogotá - Villavicencio road, in different sites that have presented instability. The soils of analysis are deposits of colluvium, which are on residual soils or the formation itself. The information provided has geomechanical parameters of the soils and of resistance thrown in direct cutting tests, standard penetration tests and retro-calculation data. The information is intended to perform statistical correlations, in order to determine equations and regression curves that allow determine factors for adjusting experimental data with retro-calculation data, and in turn serve as a reference for future studies.